Parliamentary visit to CTA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
A delegation from the joint ACP-EEC Working Group on 'Rural Development and Environmental Problems' visited the CTA on March 27,1986 to learn about the Centre's activities. Its members noted with interest the progress achieved by CTA since its...